CHALLENGES AND OPPORTUNITIES FOR MULTISECTORAL EDUCATION IMPLEMENTATION IN DISADVANTAGED AREAS: A LITERATURE REVIEW - Loso Judijanto; Rahmat Shodiqin (CV. ADIBA AISHA AMIRA, 2025)
This research explores the challenges and opportunities of implementing multisectoral education in disadvantaged areas through a literature review. The main findings identified barriers such as limited infrastructure, technology and human resources, as well as the complexity of inter-sectoral coordination and cultural barriers. However, there are significant opportunities that can be utilised, including the use of digital technology for distance learning, cross-sector collaboration to overcome funding and infrastructure limitations and the integration of local wisdom in the education curriculum. With the right strategies and collaborative efforts, the implementation of multisectoral education in disadvantaged areas has the potential to substantially improve education quality and community welfare. This study provides important insights for policymakers and education practitioners in designing and implementing inclusive and sustainable education programmes in these areas.